Response of Okra to the Application of Combined Lamtoro Liquid Organic Fertilizer and Rice Hush Ash on Growth and Chlorophyll Content - Siti Humaira; Muhibbuddin; Hafnati Rahmatan; Djufri; Samingan (Jurnal Penelitian Pendidikan IPA, 2025)
The productivity of okra (Abelmoschus esculentus L.) can be improved through the utilization of locally available organic materials, such as a combination of liquid organic fertilizer (LOF) derived from Leucaena leucocephala leaves and rice husk ash. This research aimed to evaluate the effects of the combination of these two organic inputs on the growth and chlorophyll content of okra plants. The experiment employed a factorial Completely Randomized Design (CRD) 4×4 with two factors: concentration of Leucaena-based LOF (0%, 10%, 20%, and 30%) and dosage of rice husk ash (0%, 5%, 10%, and 15%), each with three replications. Observed parameters included plant height, fresh weight, and total chlorophyll content. The results showed that the LOF treatment, rice husk ash treatment, and their interaction had significant effects (p < 0.05) on all three parameters. The combination of 30% LOF and 15% rice husk ash (A3B3) produced the highest values for plant height (62.53 cm), fresh weight (158.93 g), and total chlorophyll content (25.72 mg/L). These findings indicate that the combined application of LOF and rice husk ash can effectively enhance physiological efficiency and vegetative growth in okra plants.